The Administrative Control of Broadcasting of the Turkish Radio Television Corporation (TRT): Can the British Broadcasting Corporation (BBC) provide a Model? - Onen, S. Mustafa; Tanyildizi, Nural Imik (Ankara Haci Bayram Veli Univ, 2010)
From the past to the present day, undertaking a vital role and function during the broadcasting period requires the TRT not to go beyond its objectives and principles. By digressing from the autonomous structure during the years of its establishment, the TRT is now more dependent on the ruling power. One of the most effective ways of functioning based on legal arrangements without giving up. an honest, realistic and unbiased broadcasting policy is for administrative control to be performed 'without political bias. Determining the way to control the corporation with the help of external state-led control, in fact indicates at what level the autonomous and independent structure in the TRT is protected In this study, firstly, the institutional and legal structure of the TRT and the BBC, which is a model for public service broadcasting in the world, then their control mechanisms will be compared Finally, whether the BBC can provide a model or not will be discussed
Türkiye radyo televizyon kurumu (TRT) yayinlarinin yönetsel denetimi: İngiltere yayin kurumu (BBC) bir model olabilir mi ?
Keywords: Control; Administrative Control; Public Service Broadcasting; the TRT; the BBC